2017
DOI: 10.1016/j.buildenv.2017.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of airborne disease infection risks in an airliner cabin using the Lagrangian-based Wells-Riley approach

Abstract: a b s t r a c tAn urgent demand of assessing passengers' exposure risks in airliner cabins was raised as commercial airliners are one of the major media that carrying and transmitting infectious disease worldwide. In this study, simulations were conducted using a Boeing 737 cabin model to study the transport characteristics of airborne droplets and the associated infection risks of passengers. The numerical results of the airflow field were firstly compared against the experimental data in the literature to va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 33 publications
0
77
0
Order By: Relevance
“…9 (b), the gravitational settlement of droplets became more significant. Particularly, when the mass flow rate of droplets increased to 1000 mg, the droplets presented a remarkably changed distribution pattern, which will certainly result in different risk assessments if the assessments were based on droplet trajectories [27]. The time-dependent sizes of the representative droplets (12-μm and 112-μm) are shown in Fig.…”
Section: The Effects Of Expelled Liquid Amountmentioning
confidence: 99%
“…9 (b), the gravitational settlement of droplets became more significant. Particularly, when the mass flow rate of droplets increased to 1000 mg, the droplets presented a remarkably changed distribution pattern, which will certainly result in different risk assessments if the assessments were based on droplet trajectories [27]. The time-dependent sizes of the representative droplets (12-μm and 112-μm) are shown in Fig.…”
Section: The Effects Of Expelled Liquid Amountmentioning
confidence: 99%
“…In addition to experimental studies, computational fluid dynamics (CFD) has been used extensively in the cabin environment, to design and optimize air supply, [24][25][26][27][28] predict transient particle transport, [29][30][31] evaluate airborne infectious diseases risks, [32][33][34] and identify source location. 35,36 For example, Qian et al 32 calculated the distributions of the air velocity, air temperature, and CO 2 concentration in a section of a Boeing 767 aircraft cabin with a mixing ventilation system.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to experimental studies, computational fluid dynamics (CFD) has been used extensively in the cabin environment, to design and optimize air supply, predict transient particle transport, evaluate airborne infectious diseases risks, and identify source location . For example, Qian et al combined the CFD simulations and Wells‐Riley equation to evaluate the spatial distribution of infection risk of SARS transmission in a hospital ward.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have demonstrated that it is difficult to precisely predict the airflow, temperature, and contaminant concentration distribution in real or full-scale-mockup aircraft cabins [ 11,[22][23][24]. Specifically, it is very challenging to precisely measure the boundary conditions due to the complex geometry and limited space in the cabin.…”
Section: Contaminant Concentration Distributionmentioning
confidence: 99%